Emulating Science. The Rhetorical Figures of Creationism Emulating Science - Larissa Soares Carneiro (Journal for Religion, Film and Media, 2017)
This article compares forms of visual argumentation in the scientific study of evolution and Young-Earth Creationism, arguing that secular forms of scientific representation have affected the way creationists visually construct their own. In order to affirm their view of the origin of the universe, creationists borrow from, mimic, and ultimately emulate the techniques, or at least the appearance, of scientific method and reasoning. The use of the word "emulation" is very deliberate since their aim is to match and surpass a rival scientific paradigm - evolution. The sermon preached by the design of the Creation Museum in Petersburg, Kentucky, is not content simply to look like science, but aims to do science that is affirmed by the Scriptures.